Model Pembelajaran Berbasis Masalah dengan Pendekatan Scientific Sebagai Upaya Meningkatkan Hasil Belajar Siswa - Fadlliyah Maulidah (Reforma : Jurnal Pendidikan dan Pembelajaran, 2017)
The purpose of the use of problem-based learning model with the scientific approach is to improve student learning outcomes. This study uses a class action research design. The subject of this research is all class VIII-C SMP Wahid Hasyim Karanggeneng Methods of data collection is done by observation, tests, and questionnaires. The results showed that the management of teachers in this study increased in every meeting with both, as well as student activity also increased good. The use of problem-based learning model with this scientific approach can help to improve student learning outcomes. And students responded positively to the use of problem-based learning model with this scientific approach.Keywords: problem-based learning, scientific approach, learning outcomes